Role of Highly Sensitive Cardiac Troponin T Assay in Stable Coronary Artery Disease - Pranata, Raymond; Kusuma, Nico; Vania, Rachel; Siswanto, Bambang Budi (The Indonesian Heart Association, 2018)
Cardiac troponins (cTn) are the preferred biomarkers of myocardial necrosis, usually used for diagnosis and risk stratification in acute coronary syndromes. Highly sensitive troponin T (hs-cTnT) may be elevated in stable coronary artery disease (SCAD), in which subclinical plaque erosion or rupture and distal embolization and subclinical ischemic episode. hs-cTnT may be used as a prognostic marker in SCAD and can predict cardiovascular events and patient’s mortality rate. In this article, plaque characteristic that is linked to hs-cTnT, it’s used as prognostic biomarker and comparison to other indicators are the focus of discussion.   Abstrak Troponin adalah biomarker yang paling disukai untuk mendeteksi nekrosis miokardium dan untuk mendiagnosis dan stratifikasi risiko pada sindrom koroner akut. Highly sensitive troponin T (hs-cTnT) dapat meningkat pada penyakit jantung koroner stabil dimana terjadi ruptur plak atau erosi dan embolisasi distal sublklinis, dan episode iskemik subklinis. Sehingga biomarker tersebut dapat digunakan sebagai marker prognostik pada penyakit jantung koroner stabil dan dapat memprediksi angka kejadian kardiovaskular dan tingkat mortalitas pasien. Pada artikel ini akan dibahas mengenai karakteristik plak yang dihubungkan dengan peningkatan hs-cTnT, pengunaan sebagai biomarker prognostik dan serta perbandingan dengan indikator lainnya.